Floristic composition and species diversity of Tra Vinh University campus, Vietnam - NGHI KHAC NHU; TRINH NGOC AI; TRAN THI THAO DANG; TRAN XUAN LAM; QUAN NGOC GIAU; TRAN THI THUY DUONG; TRAN KIM NHU (Society for Indonesian Biodiversity, 2026)
Abstract. Nhu NK, Ai TN, Dang TTT, Lam TX, Giau QN, Duong TTT, Nhu TTK. 2026. Floristic composition and species diversity of Tra Vinh University campus, Vietnam. Biodiversitas 27 (2): d270230. https://doi.org/10.13057/biodiv/d270230. The floristic composition and species diversity of the Tra Vinh University (TVU) campus, an understudied Urban Green Space (UGS) in Vietnam’s Mekong Delta, were comprehensively documented through field surveys conducted during 2023-2024. Six transects covering the campus were established, and all vascular plant species occurring within 50 m on both sides of each transect were recorded, photographed, and identified using standard taxonomic references and global databases. A total of 251 species, belonging to 195 genera, 74 families, 36 orders, and 2 phyla, were documented. Of these, 143 species (57%) were identified as native to Vietnam, including 3 endemic species. The flora was dominated by Fabaceae, Poaceae, and Asteraceae, which together accounted for more than 20% of total species richness. Herbaceous plants constituted the largest life-form group (41.4%), followed by trees (22.3%) and shrubs (20.7%). Of the whole recorded species in the flora, 248 possessed documented use-values, mainly medicinal (56.6%), ornamental (18.7%), and food (16.7%) plants. Seven species were listed as threatened under the IUCN Red List or the Vietnam Red Data Book, including Pterocarpus macrocarpus and Drynaria bonii. Despite being a managed urban area, the campus supports floristic diversity comparable to that of other tropical regions in southern Vietnam. The presence of rare and threatened species underscores the role of university campuses as important refugia for urban biodiversity. These findings highlight TVU’s potential for development into a botanical garden dedicated to the long-term ex situ conservation of native and rare plant species and the restoration of urban habitats.